Online 12-step groups during the Covid-19 pandemic: A patient's perspective - Francesco Di Carlo; Maria Chiara Alessi; Elena Picutti; Mauro Pettorruso; Giovanni Martinotti; Massimo di Giannantonio (Elsevier, 2022)
Background: Following the Covid-19 pandemic, lockdown strategies have been adopted by many Governments worldwide to stop the spread of the virus. Twelve-step programs for people with substance use disorders (SUDs) as Narcotics Anonymous (NA) experienced forced interruption as well, in some cases organizing online meetings to continue their activities. The purpose of this article is to reflect on concerns and advantages of online setting for 12-step groups. Methods: We report the experience of an Italian NA participant attending for the first time an online NA group during the Covid-19 pandemic. Results: The strengths and limitations of the online setting, showing up from the living voice of this participant, are expressed in the light of the present pandemic situation. Together with the general advantages derived from telehealth technologies, specific benefits of the virtual setting for 12-step programs are shown. Concerns are also discussed, as those related to privacy and social presence. Conclusions: The case highlights many possibilities of the online setting for 12-step programs. On the other hand, it suggests the critical importance of in-person groups to accompany the recovery process. Future outcome research is needed about the combination of these approaches.